Ukrainian Classical Music in the Public Sphere Amid the Russo-Ukrainian War: 2022–2023 - Kuleba, Nataliia (Faces of War, 2025)
This article discusses the state of Ukrainian classical music during the first years of the full-scale Russian invasion, the understanding of which requires familiarity with the historical context and the rhetoric of post-colonial studies. The cultural confrontation between Ukraine and Russia reached its peak during this period, leading to a significant decline in the promotion and performance of Russian classical music both within Ukraine and internationally. Since 2022, a shift in the Ukrainian musical landscape—marked by the revitalisation of repertoire politics and an active process of derussification has been observed. This positive development is demonstrated in Ukraine’s opera houses and their ongoing repertory renewal: this includes Kateryna by Oleksandr Rodin (Odesa), Fearful Revenge by Ievhen Stankovych (Lviv), and Vyshyvanyi. The King of Ukraine by Alla Zahaikevych (Kharkiv). The Ukrainian opera Chornobyldorf by Roman Hryhoriv and Illia Razumetskyi is regarded as one of the best modern repertory operas. The staging of Genesis. Opera of Memory by the same authors in the Khanenko Museum (Kyiv, 2022) has become a new phenomenon in Ukrainian musical life. The Nova Opera group presented the Art of War opera by the young composer Serhii Vilka, based on a libretto by Myroslav Laiuk. Classical works by Ukrainian composers are also being reconceptualised: Lviv Opera presented an action version of Cossacks Beyond the Danube by Semen Hulak-Artemovskyi.Global interest in the works of Ukrainian classical music has increased; therefore, the online repository of works by local composers (the number of records on the Ukrainian Live Classic app platform rose from 500 to 1700, representing the creativity of more than 70 authors) has been developed. The renowned promoter of Ukrainian classical music is the Days of Ukrainian Music in Warsaw’ festival, which has been held since 1999 (founded by Roman Rewakowicz). The world tours of the Ukrainian Freedom Orchestra (initiated by the Metropolitan Opera and Polish National Opera) and the Kyiv Symphony Orchestra, whose programmes are based on Ukrainian music, occur within the framework of cultural diplomacy. In November 2022, during the United Kingdom–Ukraine Season of Culture, a festival of new and experimental music took place in Huddersfield with the participation of Ukrainian performers. The ‘Solidarity Project’ is an invitation from Ukrainian composers to collaborate with the Metropolitan Opera. However, there remains a lack of professional discussion regarding national classical music in the Ukrainian media landscape. Departments specialising in the post-colonial studies of Russian culture, in which Ukrainian culture has existed on the sidelines for a long time, are currently being established.